ALTERNATIF MEDIA PEMBELAJARAN DENGAN LEARNING MANAGEMENT SYSTEM MOODLE PADA FAKULTAS TEKNOLOGI INFORMASI DAN KOMUNIKASI UNIVERSITAS SEMARANG - Vensy Vydia; Nurtriana Hidayati (Jurusan Teknologi Informasi Universitas Semarang, 2016)
Learning methods development in enducation world has grown rapidly in last few years. This rapid development becomes needs for the education in Indonesia. As the Information Techonolgy has been improved, the learning methods has to be improved also, using the concept of learning management system based on information technology. This concept then well known as e-Learning , bringing a kind of learning transformation. From convensional methods becomes digital , in contents also in the systems. In this case, there is an application to run e-Learning , which is called Moodle. Moodle is one of Learning Management System tool which is usually used by education institutions. Moodle is open source software ,can be relied to meet the users needs and supplies some additional moduls.This research tried to apply Moodle as one of alternative learing model in Learning Based Competency Curriculum in the Faculty of Information Technology and Communication Universitas Semarang, especially Information System major. Try out has been done to four classes with two different lessons and some students as subject. The result is e-Learning product using Moodle as a software package . As one of evaluation subject, questionaire has been distributed to students as a research subject.